Pengaruh Teknik Relaksasi Benson Terhadap Penurunan Nyeri Pada Pasien Post Operasi Sectio Caesarea di RSUD Dr. Achmad Mochtar Bukittinggi - Kriscillia Molly Morita; Rini Amelia; Diana Putri (Jurnal Riset Hesti Medan, 2020)
Cesarean delivery is increasingly in demand by pregnant women in developed and developing countries, this is because advances in science and technology are constantly developing, especially in the field of health. Physiologically, cesarean section surgery can have a post-operative effect that is pain. Pain management in postoperative cesarean section consists of pharmacological and non-pharmacological management. One technique that can be used to reduce pain scale in a non-pharmacological way is Benson's relaxation. The purpose of this study was to determine the effect of Benson's Relaxation Techniques on Pain Reduction in Post Sectio Caesarea Patients in Dr. Achmad Mochtar Bukittinggi in 2019. This study uses Quasi Experimental with the control group. The population in this study were all post-sectio caesarea patients in the Midwifery Room of RSUD Dr. Achmad Mochtar Bukittinggi. The sample of this study was 15 intervention groups and 15 control groups taken with the Non Probality Consecutive sampling technique. Performed in April - Juli 2020. The instrument in this study uses the Numeric Rating Scale (NRS). From the 20 respondents obtained the Independent Sample T-Test parametric test results p value 0.001 (p<0.005). This means that there is an effect of Benson's Relaxation Technique on Pain Reduction in Post Sectio Caesarea Patients at RSUD Dr. Achmad Mochtar Bukittinggi in 2020. With the knowledge of the Effect of Benson Relaxation is expected to be a nursing intervention in reducing pain in post cesarean sectio patients.